KONSTRUKSI SHALAT TASBIH PADA SETIAP MALAM JUM’AT WAGE - Moh Sayid Ali Nur Kafi Ramadhani; Muhamad Nastainul Khoiri; Khoiru Yani; Alfiyan Novally Rizky; Achmad Mudzakkir Yusuf; Muhammad Anwar Idris (IAIN Syekh Nurjati Cirebon, 2022)
Tasbih prayer is worship that one of the goals is to ask forgiveness for sins that have been committed to Allah SWT. And because of Allah from. Which is evil. This paper examines what the tasbih prayer has at the An-Nur Islamic Boarding School 1 starting from the factors behind the tasbih prayer, the procedures for practicing the tasbih prayer, and also the impact that are obtained after the tasbih prayer. This paper also tells about Manaqib Shaykh Abdul Qadir al-Jailani, which is also a tradition and is read regularly after the tasbih prayer at the An-Nur Islamic Boarding School 1. The method used in this study is a qualitative research method, the data obtained from observations and interviews conducted by researchers. This paper is expected to be able to answer various questions that form the basis of the subject in this paper. The implementation of the tasbih prayer at Pondok Pesantren An-Nur 1 has a strong foundation so that it makes it a tradition and continues to be carried out to this day both by students and alumni.